F-35 Joint strike fighter : Singapore's next-generation fighter? - Wong, Kelvin Ka Weng (2013)
Defence Minister Dr Ng Eng Hen expressed the desire to replace a number of ageing air force fighter aircraft during the latest parliamentary budget debate. The Lockheed Martin F-35 Joint Strike Fighter (JSF) seems to be in the leading position to be Singapore's next-generation fighter.